2021
DOI: 10.1021/acs.jpcc.1c01716
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Few-Layer MoS2 Films: In-Situ X-ray Scattering Study During Sulfurization

Abstract: Some of the distinct optical, catalytical, and electronic properties of few-layer MoS2 films arise from a specific orientation of the MoS2 layers. The growth of horizontally or vertically aligned MoS2 during the sulfurization of predeposited Mo film can be controlled by various physical conditions such as temperature, heating rate, Mo film thickness, or sulfur vapor pressure. However, due to the inherent limitations of performing real-time and in situ experiments during sulfurization in a standard growth chamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Higher sulfur vapor pressure during sulfurization leads to the formation of vertical MoS 2 layers, while slower sulfur evaporation results in horizontally aligned layers even in the case of a thicker initial Mo layer. This finding was confirmed by an in situ X-ray scattering study …”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Higher sulfur vapor pressure during sulfurization leads to the formation of vertical MoS 2 layers, while slower sulfur evaporation results in horizontally aligned layers even in the case of a thicker initial Mo layer. This finding was confirmed by an in situ X-ray scattering study …”
Section: Introductionsupporting
confidence: 64%
“…This finding was confirmed by an in situ X-ray scattering study. 28 One of the unique properties of MoS 2 (and similar layered materials) is the ability to intercalate guest species into their van der Waals gaps. Intercalation may change the electronic structure and optical and electrical properties directly by electron doping or indirectly by inducing a phase transition or structural and compositional disorder.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The competition among growth nuclei ultimately facilitates an increase in the nucleation density on the substrate surface, thereby decreasing the coverage of the MoS 2 domains. As for the growth orientation, other researchers have demonstrated that the multioriented growth of MoS 2 domains is suppressed under a deficient Mo precursor content condition because of the higher S/Mo ratio, which helps maintain an elevated sulfur concentration, suppresses the formation of alternative species, enhances the thermodynamic stability of MoS 2 , and ultimately reduces the generation of MoS 2 with different orientations. Furthermore, appropriately increasing the S/Mo ratio improves the morphological regularity and reduces the distribution at multiorientation on the substrate.…”
Section: Resultsmentioning
confidence: 99%